Entrepreneuriat social et répression : la gestion du commerce populaire à Belo Horizonte - Tarcísio Perdigão Araújo Filho (Brésil(s))
Policies that confine street vendors to so-called popular shopping centers create an accumulation frontier, involving both public and private actors. A qualitative analysis of the Belo Horizonte case reveals coercive mechanisms that force informal workers to adapt permanently, which contradicts the thesis of voluntary adherence. Although these policies are based on a discourse linking formalization to social entrepreneurship, they are actually effective due to state repression.